Pemberdayaan Masjid Bersejarah di Kalimantan Selatan: Sebuah Upaya Transformasi Sosial Berbasis Masjid - Aziza, Aulia (Proceedings of International Conference on Da'wa and Communication, 2019)
Sultan Suriansyah Mosque is a mosque that has a great historical role for the initial milestone of the entry of Islam in the land of South Kalimantan, and historically has historical links with other mosques scattered in the South Kalimantan region. In addition to its function as a place of worship and Islamic symbols, this mosque and its region are embryos of the city of Banjarmasin. In its development the Sultan Suriansyah Mosque is now more focused and improving the development of religious tourism which later became part of an important institution capable of influencing social life both in terms of social, economic and cultural aspects. The process of transformation or life change in a more positive and better direction is very well done with mosque media as a basis for the development of the people.